Peran Ibu Sebagai Madrasatul Ula Terhadap Perkembangan Karakter Anak - Melinda Koestanti; Opik Taupik Kurahman; Dadan Rusmana (Institut Agama Islam Al-Quran Al-Ittifaqiah (IAIQI) Indralaya, 2024)
This study examines the role of mothers as madrasatul ula in the formation of children's character. As the first educator, mothers hold the main responsibility in providing early education that includes moral, spiritual, social, and intellectual values. Using a qualitative approach based on a literature study, this research identifies the various roles of mothers, ranging from providing good examples, accompanying children in every phase of growth, to creating a family environment conducive to learning. The findings show that mothers play a strategic role in shaping children's character, especially during the golden years of growth. However, challenges such as the influence of social media, work pressure, and time constraints often become obstacles for mothers in carrying out their role optimally. Therefore, a mother's readiness in terms of faith, knowledge, patience and prayer is the main key to the success of this role. The conclusion of this study emphasizes the importance of family-based education, especially the role of mothers as madrasatul ula, in building a generation with strong character, noble character, and able to adapt to the demands of the times.